Environment-friendly self-repairing flame-retardant plastic and preparation method thereof

By using plasma activation and ultrasonic treatment in degradable plastics to form composite microspheres, combined with halogen-free flame retardant, the problems of insufficient strength and flame retardancy of existing degradable plastics are solved, and self-healing and efficient flame retardant performance are achieved. Suitable for environmental protection and large-scale promotion.

CN119307038AInactive Publication Date: 2025-01-14TIANJIN GUANHUA PLASTIC PROD CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411429446.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When pursuing degradability, existing degradable plastics have poor mechanical strength, heat resistance and flame retardancy, and their dispersion is poor after adding flame retardant, resulting in reduced mechanical properties and difficult to use safely in the environment.

Method used

Polypropylene, polylactic acid, hydroxycellulose, diatomaceous earth, graphene oxide and other materials are used to form composite microspheres through plasma activation and ultrasonic treatment, combining halogen-free flame retardant and heat stabilizer to improve the dispersion and bonding of the material. Strength, enhance its self-healing ability and flame retardant properties.

Benefits of technology

The crack self-repair function of plastic is realized, mechanical strength and heat resistance are improved, flame retardant properties are enhanced, the material maintains mechanical strength at high temperatures, and is biodegradable and will not cause pollution to the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307038A_ABST
    Figure CN119307038A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of environment-friendly plastics, and particularly discloses an environment-friendly self-repairing flame-retardant plastic and a preparation method thereof. The environment-friendly self-repairing flame-retardant plastic is prepared from the following raw materials in parts by mass: 50 to 100 parts of polypropylene, 10 to 30 parts of polylactic acid, 5 to 15 parts of poly (butylene terephthalate)-adipate, 1 to 3 parts of hydroxy cellulose, 5 to 15 parts of diatomite, 1 to 5 parts of graphene oxide, 1 to 2 parts of sodium alginate, 1 to 2 parts of calcium lactate, 0.05 to 0.45 part of glutaraldehyde, 5 to 10 parts of halogen-free flame retardant, 1 to 3 parts of antioxidant and 0.5 to 1.5 parts of heat stabilizer. The flame-retardant plastic disclosed by the invention has the advantages of easily available raw materials, good environmental protection property, capability of being degraded through compost, excellent mechanical strength and self-repairing performance, good heat-resistant stability and flame retardance, simple preparation process and good biodegradability, is suitable for large-scale popularization and application, and has good economic and environmental benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of environmentally friendly plastics, and in particular to an environmentally friendly self-repairing flame-retardant plastic and a preparation method thereof. Background Art

[0002] Nowadays, plastic materials have been widely used in all aspects of people's production and life, but while bringing convenience to people, they have also brought a huge burden to environmental governance, causing serious waste of energy resources and environmental pollution.

[0003] At present, the method of incineration is adopted to deal with waste plastics, and the harmful smoke and toxic gases produced by it will also seriously pollute the natural environment. Therefore, degradable plastics came into being. Under certain environmental conditions, the connecting bonds in the molecular structure of degradable plastics break, causing certain performance losses and changes in appearance, and degrading, which is harmless or less harmful to the natural environment.

[0004] However, while existing degradable plastics focus on their own degradation rate, their mechanical strength and heat stability are significantly reduced, and their flame retardancy is poor, which greatly limits the promotion and application of degradable plastics.

[0005] CN1465618A discloses a magnesium hydroxide halogen-free flame retardant polypropylene composite material. To ensure its flame retardant effect, the added proportion of magnesium hydroxide is relatively high, and the large density limits the application range of the material.

[0006] CN108546360A discloses a flame-retardant and smoke-suppressing polypropylene composite material and a preparation method thereof, comprising polypropylene, a halogen-free flame retardant, synergistic flame-retardant microspheres, an antioxidant and a lubricant. The synergistic flame-retardant microspheres are core-shell structure microspheres, wherein the core is porous zinc stannate and the shell is microcrystalline cellulose, thereby avoiding direct contact between nano zinc stannates and between nano zinc stannate and polypropylene, thereby solving the problem of uneven dispersion of nano zinc stannate in polypropylene, but the added amount is still relatively high.

[0007] Although halogen-free flame retardants have good flame retardant effects and are environmentally friendly, the large amount of addition leads to poor dispersion in the resin matrix, forming agglomerates, and significantly reducing mechanical properties. At the same time, existing plastic materials are prone to a large number of scratches during use. Although scratch-resistant additives can be added to play a lubricating role when the parts are scratched, the scratches are still irreparable and need to be solved urgently. Summary of the invention

[0008] The purpose of the present invention is to solve the shortcomings of the prior art and to propose an environmentally friendly self-repairing flame-retardant plastic and a preparation method thereof.

[0009] An environmentally friendly self-repairing flame-retardant plastic, whose raw materials include, by mass, 50-100 parts of polypropylene, 10-30 parts of polylactic acid, 5-15 parts of polybutylene terephthalate-adipate, 1-3 parts of hydroxy cellulose, 5-15 parts of diatomaceous earth, 1-5 parts of graphene oxide, 1-2 parts of sodium alginate, 1-2 parts of calcium lactate, 0.05-0.45 parts of glutaraldehyde, 5-10 parts of halogen-free flame retardant, 1-3 parts of antioxidant, and 0.5-1.5 parts of heat stabilizer.

[0010] Preferably, the melt index of the polypropylene at 230°C (2.16 kg) is 12-16 g / 10 min.

[0011] Preferably, the melt index of the polylactic acid at 190°C (2.16 kg) is 16-19.5 g / 10 min.

[0012] Preferably, the melt index of polybutylene terephthalate-adipate at 190° C. (2.16 kg) is 3.0-6.0 g / 10 min.

[0013] Preferably, the hydroxycellulose is at least one of hydroxypropyl cellulose, hydroxypropyl methyl cellulose and hydroxyethyl cellulose.

[0014] Preferably, the halogen-free flame retardant is at least one of melamine pyrophosphate, melamine cyanurate, triphenyl phosphate and aluminum hypophosphite.

[0015] Preferably, the heat stabilizer is a calcium zinc stabilizer or methyl tin mercaptan.

[0016] The method for preparing the above-mentioned environmentally friendly self-repairing flame-retardant plastic comprises the following steps:

[0017] S1. Send polypropylene into an ammonia plasma instrument for treatment for 10-20 seconds at a treatment power of 120-150W to obtain activated polypropylene;

[0018] S2, adding hydroxycellulose and diatomaceous earth to water, ultrasonicating at room temperature for 1-2 hours, adding sodium alginate and calcium lactate thereto, stirring evenly, drying at 40-46°C, crushing to obtain microspheres, spraying glutaraldehyde solution on the surface under stirring, keeping warm at 40-45°C for 1-2 hours, and freeze-drying to obtain composite microspheres;

[0019] S3. Add activated polypropylene and composite microspheres into deionized water and ultrasonically treat for 1-2 hours, filter, dry, add graphene oxide, polylactic acid, polybutylene terephthalate-adipate, mix evenly, and add from the main feed port of the twin-screw extruder; mix the halogen-free flame retardant, antioxidant, and heat stabilizer evenly, add from the side feed port of the twin-screw extruder, melt blend at 195-210°C, extrude, and granulate.

[0020] Preferably, in S2, the ultrasonic frequency is 3-8 kHz.

[0021] Preferably, in S2, the mass fraction of the glutaraldehyde solution is 5-15%.

[0022] Preferably, in S3, the ultrasonic frequency is 10-30 kHz.

[0023] Beneficial effects:

[0024] The present invention forms active amino groups on the surface of polypropylene by plasma activation, thereby greatly enhancing the reactivity of polypropylene. Diatomaceous earth is rich in a large number of active void structures to load hydroxy cellulose, and is coated with sodium alginate and calcium lactate. The solidified microspheres have high stability and are combined with activated polypropylene. Compared with direct blending of hydroxy cellulose, diatomaceous earth and polypropylene, the present invention has better dispersion uniformity and high bonding strength. When cracks appear in the plastic, the internal hydroxy cellulose and graphene oxide both contain rich oxygen-containing groups and can be tightly combined through hydrogen bonding, with excellent self-repairing effect.

[0025] The present invention not only has the function of self-repairing cracks, but also allows air and moisture to fully enter the cracks with the cooperation of diatomaceous earth when cracks occur. The cracks are combined through hydrogen bonds between oxygen-containing groups in the present invention, and a stable structure is formed after drying. The crack self-repairing effect is excellent. If cracks occur again, the crack self-repairing ability is still possessed, and the advantages of durability and good mechanical properties are also possessed.

[0026] The present invention adopts activated polypropylene to match with polylactic acid and polybutylene terephthalate-adipate, and the compatibility between them is good, and no additional compatibilizer needs to be added. The system has excellent molding and processing performance, and the tensile strength and bending strength of the plastic system are high. The halogen-free flame retardant has good dispersibility therein and is beneficial to improving the flame retardant performance of the material system, so that the obtained plastic material system can still maintain a certain mechanical strength for a long time at a higher temperature, is not easy to generate toxic and harmful gases, and has higher safety in use.

[0027] The raw materials of the flame-retardant plastic obtained by the present invention are easily available, and the product is green and environmentally friendly. It can be degraded by composting after use, has good biodegradability, and will not cause a burden on the environment. The material not only has excellent mechanical strength and self-repairing performance, but also has good heat stability and flame retardancy. The preparation process is simple, and the product is suitable for large-scale promotion and use, with good economic and environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a comparison chart of the tensile strength and bending strength of the environmentally friendly self-healing flame-retardant plastics obtained in Example 5 and Comparative Examples 1-2.

[0029] Figure 2It is a comparison chart of the tensile strength retention rate and the bending strength retention rate of the environmentally friendly self-healing flame-retardant plastics obtained in Example 5 and Comparative Examples 1-2.

[0030] Figure 3 This is a comparison chart of the scratch resistance and scratch automatic repair performance of the environmentally friendly self-repairing flame retardant plastics obtained in Example 5 and Comparative Examples 1-2.

[0031] Figure 4 It is a comparison chart of the oxygen index of the environmentally friendly self-healing flame-retardant plastics obtained in Example 5 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0032] The present invention will be further explained below in conjunction with specific embodiments.

[0033] The polypropylene used in the following description is from Zhenhai Petrochemical Company, with the brand name PP Z30S. Upon inspection upon entry into the warehouse, its melt index (230° C., 2.16 kg) is 10 g / 10 min.

[0034] The polylactic acid used below was purchased from Zhejiang Mouzheng Biomaterial Co., Ltd. with the brand name PLA REVODE 210. After inspection upon entry into the warehouse, its melt index (190° C., 2.16 kg) was 17.6 g / 10 min.

[0035] The polybutylene terephthalate-adipate used below was purchased from Hangzhou Moufeng New Materials Co., Ltd. with the brand name PBAT DP-9324NC. After inspection upon entry into the warehouse, its melt index (190°C, 2.16kg) was 6.0g / 10min.

[0036] The calcium zinc stabilizer used below was purchased from Ningbo Bingmu Plastic Technology Co., Ltd.

[0037] Example 1

[0038] An environmentally friendly self-repairing flame-retardant plastic, whose raw materials include: 60kg of polypropylene, 10kg of polylactic acid, 5kg of polybutylene terephthalate-adipate, 1kg of hydroxyethyl cellulose, 5kg of diatomaceous earth, 1kg of graphene oxide, 1kg of sodium alginate, 1kg of calcium lactate, 0.05kg of glutaraldehyde, 5kg of melamine pyrophosphate, 1kg of antioxidant 10101kg, and 0.5kg of methyl tin mercaptan.

[0039] The method for preparing the above-mentioned environmentally friendly self-repairing flame-retardant plastic comprises the following steps:

[0040] S1. Send polypropylene into an ammonia plasma instrument for treatment for 10 seconds at a treatment power of 120W to obtain activated polypropylene;

[0041] S2, adding hydroxyethyl cellulose and diatomaceous earth to 10 kg of water, ultrasonicating at room temperature for 1 hour, the ultrasonic frequency is 3 kHz, adding sodium alginate and calcium lactate thereto, stirring evenly, drying at a temperature of 40°C, crushing to obtain microspheres with a particle size of 1 mm, spraying a 5% by mass glutaraldehyde solution on the surface under stirring, keeping warm at a temperature of 40°C for 1 hour, and freeze-drying to obtain composite microspheres;

[0042] S3. Add activated polypropylene and composite microspheres into 30 kg of deionized water and perform ultrasonic treatment for 1 hour at an ultrasonic frequency of 10 kHz. Filter and dry. Add graphene oxide, polylactic acid and polybutylene terephthalate-adipate and mix evenly. Add them from the main feed port of a twin-screw extruder. Mix melamine pyrophosphate, antioxidant 1010 and methyl tin mercaptan evenly and add them from the side feed port of a twin-screw extruder. The twin-screw extruder has a screw length-to-diameter ratio of 15:1. Melt blend at a temperature of 195°C, extrude and granulate.

[0043] Example 2

[0044] An environmentally friendly self-repairing flame-retardant plastic, whose raw materials include: 100kg of polypropylene, 30kg of polylactic acid, 15kg of polybutylene terephthalate-adipate, 3kg of hydroxypropyl methylcellulose, 15kg of diatomaceous earth, 5kg of graphene oxide, 2kg of sodium alginate, 2kg of calcium lactate, 0.45kg of glutaraldehyde, 10kg of melamine cyanurate, 10103kg of antioxidant, and 1.5kg of methyl tin mercaptan.

[0045] The method for preparing the above-mentioned environmentally friendly self-repairing flame-retardant plastic comprises the following steps:

[0046] S1. Send polypropylene into an ammonia plasma instrument for treatment for 20 seconds at a treatment power of 150W to obtain activated polypropylene;

[0047] S2, adding hydroxypropyl methylcellulose and diatomaceous earth to 20 kg of water, ultrasonicating at room temperature for 2 hours at an ultrasonic frequency of 8 kHz, adding sodium alginate and calcium lactate thereto and stirring evenly, drying at a temperature of 46°C, crushing to obtain microspheres with a particle size of 2 mm, spraying a glutaraldehyde solution with a mass fraction of 15% on the surface while stirring, keeping warm at a temperature of 45°C for 2 hours, and freeze-drying to obtain composite microspheres;

[0048] S3. Add activated polypropylene and composite microspheres into 60 kg of deionized water and perform ultrasonic treatment for 2 hours at an ultrasonic frequency of 30 kHz. Filter and dry. Add graphene oxide, polylactic acid and polybutylene terephthalate-adipate and mix evenly. Add them from the main feed port of a twin-screw extruder. Mix melamine cyanurate, antioxidant 1010 and methyl tin mercaptan evenly and add them from the side feed port of a twin-screw extruder. The screw length-diameter ratio of the twin-screw extruder is 20:1. Melt blending, extrusion and granulation are performed at a temperature of 210°C.

[0049] Example 3

[0050] An environmentally friendly self-repairing flame-retardant plastic, whose raw materials include: 70kg of polypropylene, 25kg of polylactic acid, 8kg of polybutylene terephthalate-adipate, 2.5kg of hydroxypropyl cellulose, 8kg of diatomaceous earth, 4kg of graphene oxide, 1.3kg of sodium alginate, 1.8kg of calcium lactate, 0.15kg of glutaraldehyde, 6kg of melamine cyanurate, 3kg of triphenyl phosphate, 1.5kg of antioxidant 1010, and 1.2kg of calcium zinc stabilizer.

[0051] The method for preparing the above-mentioned environmentally friendly self-repairing flame-retardant plastic comprises the following steps:

[0052] S1, sending polypropylene into an ammonia plasma instrument for treatment for 12 seconds, with a treatment power of 140W to obtain activated polypropylene;

[0053] S2, adding hydroxypropyl cellulose and diatomaceous earth to 12 kg of water, ultrasonicating at room temperature for 100 min at an ultrasonic frequency of 4 kHz, adding sodium alginate and calcium lactate thereto and stirring evenly, drying at a temperature of 44°C, crushing to obtain microspheres with a particle size of 1.5 mm, spraying a glutaraldehyde solution with a mass fraction of 8% on the surface while stirring, keeping the mixture at a temperature of 43°C for 80 min, and freeze-drying to obtain composite microspheres;

[0054] S3. Add activated polypropylene and composite microspheres into 50 kg of deionized water and perform ultrasonic treatment for 80 minutes at an ultrasonic frequency of 27 kHz. Filter and dry. Add graphene oxide, polylactic acid and polybutylene terephthalate-adipate and mix evenly. Add the mixture from the main feed port of a twin-screw extruder. Mix melamine cyanurate, triphenyl phosphate, antioxidant 1010 and calcium zinc stabilizer evenly and add the mixture from the side feed port of the twin-screw extruder. The twin-screw extruder has a screw length-to-diameter ratio of 17:1. Melt blending, extrusion and granulation are performed at a temperature of 208°C.

[0055] Example 4

[0056] An environmentally friendly self-repairing flame-retardant plastic, whose raw materials include: 90kg of polypropylene, 15kg of polylactic acid, 12kg of polybutylene terephthalate-adipate, 1.5kg of hydroxypropyl cellulose, 12kg of diatomaceous earth, 2kg of graphene oxide, 1.7kg of sodium alginate, 1.2kg of calcium lactate, 0.35kg of glutaraldehyde, 7kg of aluminum hypophosphite, 2.5kg of antioxidant 1010, and 0.8kg of calcium zinc stabilizer.

[0057] The method for preparing the above-mentioned environmentally friendly self-repairing flame-retardant plastic comprises the following steps:

[0058] S1, sending polypropylene into an ammonia plasma instrument for treatment for 18 seconds, with a treatment power of 130W to obtain activated polypropylene;

[0059] S2, adding hydroxypropyl cellulose and diatomaceous earth to 18 kg of water, ultrasonicating at room temperature for 80 min at an ultrasonic frequency of 7 kHz, adding sodium alginate and calcium lactate thereto and stirring evenly, drying at a temperature of 42°C, crushing to obtain microspheres with a particle size of 1.5 mm, spraying a glutaraldehyde solution with a mass fraction of 12% on the surface while stirring, keeping the temperature at 41°C for 100 min, and freeze-drying to obtain composite microspheres;

[0060] S3. Add activated polypropylene and composite microspheres into 40 kg of deionized water and ultrasonically treat for 100 min at an ultrasonic frequency of 15 kHz. Filter and dry. Add graphene oxide, polylactic acid and polybutylene terephthalate-adipate and mix evenly. Add them from the main feed port of a twin-screw extruder. Mix aluminum hypophosphite, antioxidant 1010 and calcium zinc stabilizer evenly and add them from the side feed port of the twin-screw extruder. The screw length-diameter ratio of the twin-screw extruder is 19:1. Melt blending, extrusion and granulation are performed at a temperature of 200°C.

[0061] Example 5

[0062] An environmentally friendly self-repairing flame-retardant plastic, whose raw materials include: 80kg of polypropylene, 20kg of polylactic acid, 10kg of polybutylene terephthalate-adipate, 2kg of hydroxypropyl cellulose, 10kg of diatomaceous earth, 3kg of graphene oxide, 1.5kg of sodium alginate, 1.5kg of calcium lactate, 0.25kg of glutaraldehyde, 8kg of triphenyl phosphate, 10102kg of antioxidant, and 1kg of calcium zinc stabilizer.

[0063] The method for preparing the above-mentioned environmentally friendly self-repairing flame-retardant plastic comprises the following steps:

[0064] S1. The polypropylene is sent into an ammonia plasma instrument for treatment for 15 seconds at a treatment power of 135W to obtain activated polypropylene;

[0065] S2, adding hydroxypropyl cellulose and diatomaceous earth to 15 kg of water, ultrasonicating at room temperature for 90 min at an ultrasonic frequency of 6 kHz, adding sodium alginate and calcium lactate thereto and stirring evenly, drying at a temperature of 43°C, crushing to obtain microspheres with a particle size of 1.5 mm, spraying a glutaraldehyde solution with a mass fraction of 10% on the surface while stirring, keeping the temperature at 42°C for 90 min, and freeze-drying to obtain composite microspheres;

[0066] S3. Add activated polypropylene and composite microspheres into 45 kg of deionized water and perform ultrasonic treatment for 90 minutes at an ultrasonic frequency of 21 kHz. Filter and dry. Add graphene oxide, polylactic acid and polybutylene terephthalate-adipate and mix evenly. Add them from the main feed port of a twin-screw extruder. Mix triphenyl phosphate, antioxidant 1010 and calcium zinc stabilizer evenly and add them from the side feed port of a twin-screw extruder. The screw length-diameter ratio of the twin-screw extruder is 18:1. Melt blending, extrusion and granulation are performed at a temperature of 205°C.

[0067] Comparative Example 1

[0068] An environmentally friendly self-repairing flame-retardant plastic, whose raw materials include: 80kg of polypropylene, 20kg of polylactic acid, 10kg of polybutylene terephthalate-adipate, 2kg of hydroxypropyl cellulose, 10kg of diatomaceous earth, 3kg of graphene oxide, 1.5kg of sodium alginate, 1.5kg of calcium lactate, 0.25kg of glutaraldehyde, 8kg of triphenyl phosphate, 10102kg of antioxidant, and 1kg of calcium zinc stabilizer.

[0069] The method for preparing the above-mentioned environmentally friendly self-repairing flame-retardant plastic comprises the following steps:

[0070] S1. Add hydroxypropyl cellulose and diatomaceous earth to 15 kg of water, perform ultrasonic treatment at room temperature for 90 min at an ultrasonic frequency of 6 kHz, add sodium alginate and calcium lactate, stir evenly, dry at 43°C, and grind to obtain microspheres with a particle size of 1.5 mm. Spray a 10% glutaraldehyde solution on the surface while stirring, keep warm at 42°C for 90 min, and freeze-dry to obtain composite microspheres.

[0071] S2. Add polypropylene and composite microspheres to 45 kg of deionized water and perform ultrasonic treatment for 90 minutes at an ultrasonic frequency of 21 kHz. Filter and dry. Add graphene oxide, polylactic acid, and polybutylene terephthalate-adipate and mix evenly. Add the mixture from the main feed port of a twin-screw extruder. Mix triphenyl phosphate, antioxidant 1010, and calcium zinc stabilizer evenly and add the mixture from the side feed port of the twin-screw extruder. The twin-screw extruder has a screw length-to-diameter ratio of 18:1. Melt blending, extrusion, and granulation are performed at a temperature of 205°C.

[0072] Comparative Example 2

[0073] An environmentally friendly self-repairing flame-retardant plastic, whose raw materials include: 80kg of polypropylene, 20kg of polylactic acid, 10kg of polybutylene terephthalate-adipate, 2kg of hydroxypropyl cellulose, 10kg of diatomaceous earth, 3kg of graphene oxide, 1.5kg of sodium alginate, 1.5kg of calcium lactate, 0.25kg of glutaraldehyde, 8kg of triphenyl phosphate, 10102kg of antioxidant, and 1kg of calcium zinc stabilizer.

[0074] The method for preparing the above-mentioned environmentally friendly self-repairing flame-retardant plastic comprises the following steps:

[0075] S1. The polypropylene is sent into an ammonia plasma instrument for treatment for 15 seconds at a treatment power of 135W to obtain activated polypropylene;

[0076] S2, adding diatomaceous earth to 15 kg of water, ultrasonicating at room temperature for 90 min at an ultrasonic frequency of 6 kHz, adding sodium alginate and calcium lactate thereto and stirring evenly, drying at a temperature of 43° C., crushing to obtain microspheres with a particle size of 1.5 mm, spraying a 10% glutaraldehyde solution on the surface under stirring, keeping the temperature at 42° C. for 90 min, and freeze-drying to obtain composite microspheres;

[0077] S3. Add activated polypropylene and composite microspheres into 45 kg of deionized water and perform ultrasonic treatment for 90 min at an ultrasonic frequency of 21 kHz. Filter and dry. Add graphene oxide, hydroxypropyl cellulose, polylactic acid and polybutylene terephthalate-adipate and mix evenly. Add the mixture from the main feed port of a twin-screw extruder. Mix triphenyl phosphate, antioxidant 1010 and calcium zinc stabilizer evenly and add the mixture from the side feed port of a twin-screw extruder. The twin-screw extruder has a screw length-to-diameter ratio of 18:1. Melt blending is performed at a temperature of 205°C, followed by extrusion and granulation.

[0078] The tensile strength of the environmentally friendly self-healing flame-retardant plastics obtained in Example 5 and Comparative Examples 1-2 was measured with reference to GB / T 1040.2-2022 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics".

[0079] The bending strength of the environmentally friendly self-repairing flame-retardant plastics obtained in Example 5 and Comparative Examples 1-2 was measured with reference to GB / T 9341-2008 “Determination of Flexural Properties of Plastics”.

[0080] like Figure 1 As shown, the tensile strength and bending strength of the environmentally friendly self-healing flame-retardant plastic obtained in Example 5 are the highest, which are better than those of Comparative Examples 1-2 (P < 0.05).

[0081] The environmentally friendly self-healing flame-retardant plastics obtained in Example 5 and Comparative Examples 1-2 were placed in a 50°C 65% RH environment for a heat stability test, and the tensile strength and bending strength of each group of samples were measured again, and the tensile strength retention rate and bending strength retention rate were calculated.

[0082] Tensile strength / bending strength retention rate = tensile strength / bending strength after heat stability test ÷ original tensile strength / bending strength × 100%

[0083] like Figure 2As shown, the tensile strength retention rate and bending strength retention rate of the environmentally friendly self-healing flame-retardant plastic obtained in Example 5 are the highest, which are better than those of Comparative Examples 1-2 (P < 0.05).

[0084] The environmentally friendly self-repairing flame-retardant plastics obtained in Example 5 and Comparative Examples 1-2 were tested for scratch resistance and scratch automatic repair performance. The details are as follows:

[0085] (1) The scratch resistance test was conducted using the PV3952 Volkswagen scratch resistance test, and the dL characterization (immediate test) was used.

[0086] (2) The scratch self-repair performance was tested by injection molding each group of samples into leather pattern panels, and the scratch force used in the test was 10 N. The self-repair temperature was 23±2℃, the time was 30 min, and the △L was tested after 15 min of placement for comparison.

[0087] Scratch resistance is expressed by △L value, L represents whiteness, and △L represents the whiteness value after scratch minus the whiteness value before scratch. After automatic repair, △L becomes smaller, indicating that self-repair has occurred.

[0088] like Figure 3 As shown, the dL of the sample in Example 5 is the smallest, indicating that the scratch resistance of Example 5 is the best. The ΔL of each group of samples is decreasing, indicating that each group of samples has self-repaired, but the ΔL of the sample in Comparative Example 2 decreases the least, while the ΔL of the sample in Example 5 decreases the most, indicating that the self-repair performance of Example 5 is the best.

[0089] The oxygen index of the environmentally friendly self-healing flame-retardant plastics obtained in Example 5 and Comparative Examples 1-2 was measured with reference to GB / T 2406.1-2008 "Determination of Combustion Behavior of Plastics by Oxygen Index Method Part 1: Guidelines".

[0090] like Figure 4 As shown, the oxygen index of the environmentally friendly self-repairing flame-retardant plastic obtained in Example 5 is the highest, which is better than that of Comparative Examples 1-2 (P < 0.05).

[0091] The applicant believes that this is because the present invention forms active amino groups on the surface of polypropylene through plasma activation, which greatly enhances the reactivity of polypropylene; and diatomaceous earth is rich in a large number of active void structures for loading hydroxy cellulose, and is coated with sodium alginate and calcium lactate. The solidified microspheres have high stability, and combined with activated polypropylene, not only the dispersion uniformity is better, but also the bonding strength is high. When cracks appear in the plastic, the internal hydroxy cellulose and graphene oxide both contain rich oxygen-containing groups, which can be tightly combined through hydrogen bonding. When cracks occur, the present invention allows air and moisture to fully enter the cracks with the cooperation of diatomaceous earth, and the cracks are combined through the hydrogen bonding between the oxygen-containing groups in the present invention. With the formation of a stable structure after drying, the crack self-repair effect is excellent. If cracks occur again, the crack self-repair ability is still possessed, and the advantages of good durability and mechanical properties are also combined. The present invention adopts activated polypropylene to match with polylactic acid and polybutylene terephthalate-adipate, and the compatibility between them is good, and no additional compatibilizer needs to be added. The system has excellent molding and processing performance, and the tensile strength and bending strength of the plastic system are high. The halogen-free flame retardant has good dispersibility therein and is beneficial to improving the flame retardant performance of the material system, so that the obtained plastic material system can still maintain a certain mechanical strength for a long time at a higher temperature, is not easy to generate toxic and harmful gases, and has higher safety in use.

[0092] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An environmentally friendly self-repairing flame-retardant plastic, characterized in that: The raw materials include, by mass, 50-100 parts of polypropylene, 10-30 parts of polylactic acid, 5-15 parts of polybutylene terephthalate-adipate, 1-3 parts of hydroxy cellulose, 5-15 parts of diatomaceous earth, 1-5 parts of graphene oxide, 1-2 parts of sodium alginate, 1-2 parts of calcium lactate, 0.05-0.45 parts of glutaraldehyde, 5-10 parts of halogen-free flame retardant, 1-3 parts of antioxidant and 0.5-1.5 parts of heat stabilizer.

2. The environmentally friendly self-repairing flame-retardant plastic according to claim 1, characterized in that: The melt index of polypropylene at 230°C 2.16 kg is 12-16 g / 10 min.

3. The environmentally friendly self-repairing flame-retardant plastic according to claim 1, characterized in that: The melt index of polylactic acid at 190°C and 2.16 kg is 16-19.5 g / 10 min.

4. The environmentally friendly self-repairing flame-retardant plastic according to claim 1, characterized in that: The melt index of polybutylene terephthalate-adipate at 190°C (2.16 kg) is 3.0-6.0 g / 10 min.

5. The environmentally friendly self-repairing flame-retardant plastic according to claim 1, characterized in that: The hydroxycellulose is at least one of hydroxypropyl cellulose, hydroxypropyl methyl cellulose and hydroxyethyl cellulose.

6. The environmentally friendly self-repairing flame-retardant plastic according to claim 1, characterized in that: The halogen-free flame retardant is at least one of melamine pyrophosphate, melamine cyanurate, triphenyl phosphate and aluminum hypophosphite.

7. The environmentally friendly self-repairing flame-retardant plastic according to claim 1, characterized in that: The heat stabilizer is calcium zinc stabilizer or methyl tin mercaptan.

8. A method for preparing the environmentally friendly self-repairing flame-retardant plastic according to any one of claims 1 to 7, characterized in that: The steps include: S1. Send polypropylene into an ammonia plasma instrument for treatment for 10-20 seconds at a treatment power of 120-150W to obtain activated polypropylene; S2, adding hydroxycellulose and diatomaceous earth to water, ultrasonicating at room temperature for 1-2 hours, adding sodium alginate and calcium lactate thereto, stirring evenly, drying at 40-46°C, crushing to obtain microspheres, spraying glutaraldehyde solution on the surface under stirring, keeping warm at 40-45°C for 1-2 hours, and freeze-drying to obtain composite microspheres; S3. Add activated polypropylene and composite microspheres into deionized water and ultrasonically treat for 1-2 hours, filter, dry, add graphene oxide, polylactic acid, polybutylene terephthalate-adipate, mix evenly, and add from the main feed port of the twin-screw extruder; mix the halogen-free flame retardant, antioxidant, and heat stabilizer evenly, add from the side feed port of the twin-screw extruder, melt blend at 195-210°C, extrude, and granulate.

9. The method for preparing the environmentally friendly self-repairing flame-retardant plastic according to claim 8, characterized in that: In S2, the ultrasonic frequency is 3-8 kHz; in S3, the ultrasonic frequency is 10-30 kHz.

10. The method for preparing the environmentally friendly self-repairing flame-retardant plastic according to claim 8, characterized in that: In S2, the mass fraction of the glutaraldehyde solution is 5-15%.

Citation Information

Patent Citations

  • Flame-retarding and smoke-suppressing polypropylene composite material and preparation method thereof

    CN108546360A